Generational Inequalities and Political Practices among Paraguayan Migrant Youths in Buenos Aires - Gavazzo, Natalia; Gerbaudo Suárez, Débora (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2020)
The objective of the article is to analyze the Paraguayan migration to Buenos Aires, the focus on generational relations and its impact on the construction of agency among youth immigrants. Based on an ethnographic approach, we address the genealogical, age and socio-political relationships between different generations, both in the family sphere and in immigrant organizations. In conclusion, there are intergenerational inequalities conditioning political practices and the construction of agency between young people. Nonetheless, we observe the combination of different strategies and of capitals, like “militant capital”, that the youths develop to dispute power with the previous generation. Finally, we advance in the generational construction that young people make through their own organizations and from which they seek to legitimize their political action.
Keywords: migrant youth; Paraguay; generations; inequalities; agency; political practices